Impact of Business Cycles on Innovation Activity of Enterprises in EU Countries - Kijek, Arkadiusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Multidimensional connections between innovative activity of enterprises and business cycle phases result in the ambiguous nature of this relationship. The main aim of the article is to analyze the impact of business cycle phases on inputs and outputs of innovative activity of enterprises. The innovative performance of companies was examined during periods of recession and recovery in the EU countries and in Norway in the years 2002–2014. Empirical verification of theoretical assumptions confirmed the complex nature of the relationship between the innovative activity of enterprises and business cycles.